Surgical resection for adrenocortical carcinoma: Current trends affecting survival. Issue 8 (14th March 2022) - Shah, Monali; NeMoyer, Rachel E.; Kashyap, Richi; Lin, Yong; Sarmiento, Juan; Kooby, David A.; Maithel, Shishir K.; Gillespie, Theresa W.; Laird, Amanda M.; Shah, Mihir M.
Abstract: Introduction: Adrenocortical carcinoma (ACC) is associated with a poor prognosis. We reviewed the National Cancer Database (NCDB) to analyze the prognostic factors in surgically resected ACC patients and the association of surgical approaches with overall survival (OS). Methods: A retrospective NCDB (2004–2014) review of patients undergoing curative‐intent surgical resection for ACC was performed. Effects of patient demographics, tumor characteristics, histopathology, and perioperative course on OS were analyzed. Log‐rank statistics were used to associate clinical variables with OS. The multivariable Cox proportional hazard model included only statistically significant variables. Results: A total of 1599 patients with ACC were included. A majority of patients were female (60.73%) and presented with a Charlson–Deyo score of zero (75.42%). A majority of the ACC cases were Grade 3 (45.69%), and almost a third (30.64%) underwent margin‐positive resections. Univariate analysis demonstrated a decrease in OS associated with increasing age and comorbidities. A negative resection margin and lack of lymphovascular invasion predicted better OS. Multivariable analysis showed that age, grade, surgical resection margins, and hospital length of stay were associated with OS. Conclusions: Advanced age, grade, presence of lymphovascular invasion, and positive surgical margins predicted a worse overall survival for adrenocortical cancer in our analysis. Resection with negative margins improves outcomes.